Where is the Third E in Controlling Coronavirus Disease-19 in Indonesia? A Mini Review - Sirait, Paul; Zaluchu, Fotarisman (Open Access Macedonian Journal of Medical Sciences, 2021)
Coronavirus disease (COVID-19) continues to attract global attention and is the most serious health problem today. Indonesia faces a very significant spike in cases in mid-2021. This may be related to inadequate enforcement before cases reach their peak. To review what has happened and what should be done in the future, this paper presents the three Es concept to be applied more consistently in efforts to control COVID-19 in Indonesia.